A Model Of Residential Land Distribution Policy In Oman Based On Al-ᶜAdl Wa Al-Iḥsān: A Case Study Of Muscat Governorate - Jamal Al Maimani (Universiti Sains Islam Malaysia, 2024)
Residential land distribution by the government in Oman captures the interest of the citizens because this is dependent on their top priority concern of buying or building a house. Such an issue is considered the number one social dilemma for many young people. The government holds the responsibility of residential land distribution to the citizens in Oman. Muscat Governorate is one of the most critical regions in Oman because it comprises famous cities, including the capital city Muscat. Therefore, Muscat Governorate has attracted many citizens as residency location due to its modern development and job station on both levels both government and private sector. This study will focus on residential land distribution in Muscat Governorate. Also, how the government officials were able to meet and fulfil the concept of al-ᶜAdl wa al-Iḥsān related to land distribution for the citizens as the main problem statement of this study. The theorization of justice has deeply been rooted in the Islamic message since revelation of al-qurān. Also, in the practice of the Prophet (PBUH) and early Muslims. For the purpose of exploring the best practice and solution in fulfilling land distribution, a qualitative approach study was applied at the Muscat Governorate. Several assumptions were outlined to get the gathered and analyzed data of appropriate number of respondents such as the time required to acquire land, the size of the area granted, the location of the land with Muscat Governorate and finally the availability of infrastructure and services when the plots were distributed to the citizens. All these aspects will be analyzed in light of Islamic social justice to find out how this practice achieved its goal. The end of the study has found that the ideal land distribution period, according to al-ᶜAdl wa al-Iḥsān should be is 1-5 years. As the ideal for applicant age 21-23 years old, land size of 600 square meters, location within Muscat or outside Muscat with several options of an appropriate model. Such implementation was found useful and successful for both, the citizens and the government. Thus, the thesis recommends the ideal model, among the discussed options, which satisfies the parameters of land distribution based on al-ᶜAdl wa alIḥsān.